Delayed Diagnosis of Early-onset Sarcoidosis: A Case Report and Literature Review - Al-essi, Mutibah Ali; Binkhamis, Lujain Salah; Aljohani, Samah Mohammed; Alzahrani, Nora Mohammad (Journal of Advanced Pediatrics and Child Health, 2024)
Background: Early-onset sarcoidosis is a rare systemic inflammatory granulomatous disease, distinguished by onset before the age of 4 and notably lacking pulmonary involvement. Unfortunately, the condition often shows clinical features similar to juvenile idiopathic arthritis, resulting in the misdiagnosis of numerous patients. This case report delves into the challenges associated with the delayed diagnosis of early-onset sarcoidosis, with a particular focus on the diagnostic methods employed to address this delayed recognition. Case presentation: A 15-year-old girl presented with a history of recurrent fever since infancy, accompanied by rash, arthritis, and joint deformity. Previously misdiagnosed with juvenile idiopathic arthritis, she underwent management with steroids and methotrexate, yielding no improvement. The diagnosis of early-onset sarcoidosis was made during adolescence based on serial examinations, comprehensive laboratory and radiological evaluations, and subsequent histopathology findings. Presently, the patient is receiving treatment with low-dose steroids and biologic therapy (Tocilizumab) and experiencing no disease progression. Conclusion: This case report underscores the importance of considering early-onset sarcoidosis in the differential diagnosis of pediatric patients exhibiting persistent arthritis from an early age. Early detection and treatment are crucial in averting complications and enhancing the overall quality of life.